The Relevance of Bernard Shaw to Our Times - Rao, E. Nageswara (EAST WEST JOURNAL OF HUMANITIES, 2010)
Abstract Conirary to gential as‘umptiton. Bernard Shaw’s writing have contemporary relevance. His views on ttuelty to animals. censorship. democracy. medical profession. women’s status CI r.. are all live Issues even today. His plea tin 11.11111aNi011 fur all coral tires is timely because of the mass slaughter of animals and birds, He disapproved censorship since It delays enlightenment. His comparison of tleimwracy m a balloon. stampede and auctim: is appropriate now. fits expose of the medical profession anticipates its unethical practices. He championed women’s none before len:ittime Iwcame known. Shaw was far ahead of his times. Hence his ideas have continued relevance to us. These (prefaces rf mine an no awn ow rf date than the ds. or (Jtopia. or Ton: Junes. or Little Dorrit. or err, she plats of ttrinophann and Euripides and she Socrarian Askew of Plato -George Bernard Shaw 0938)